The Potential of Generative AI tools such as ChatGPT for Sustainable Business Model Innovation - Daniel Duwe; Marion A. Weissenberger-Eibl (Fraunhofer-Gesellschaft zur Förderung der angewandten Forschung; ZBW - Leibniz Information Centre for Economics, 2024)
Megatrends such as sustainability force companies to adjust their business models or even to create entirely new ones. However, many companies struggle to do so be-cause of multiple reasons such as lacking creativity and capacity. The advent of Generative AI tools such as ChatGPT can help to overcome this challenge. In this paper, it was analyzed if and how Generative AI can be used to develop innovative business models and whether the results are of the same quality as compared to the ones from human origin.
Conference: R&D Management Conference 2024, June 17-19, 2024, Stockholm, Sweden, organized by the KTH Royal Institute of Technology
Keywords: 650; Business model innovation; Sustainability; Generative artificial intelligence